# Chapter 23 Homework 3: Poisson Process, Birth and Death Process: Problems and Tentative Solutions

Exercise 23.1 (Birth process, probability of even and odd number of occurence) Let $$X(t)$$ be a pure birth continuous time Markov chain. Assume that $\begin{equation} \begin{split} &P(\text{an event happen in (t,t+h)}|X(t)=\text{odd})=\lambda_1h+o(h)\\ &P(\text{an event happen in (t,t+h)}|X(t)=\text{even})=\lambda_2h+o(h) \end{split} \tag{23.1} \end{equation}$ where $$\frac{o(h)}{h}\to 0$$ as $$h\to 0$$. Take $$X(0)=0$$. Find the following probabilities: $$P_1(t)=P(X(t)=\text{odd})$$ and $$P_2(t)=P(X(t)=\text{even})$$.

Hint: Derive the differential equations: $\begin{equation} \begin{split} &P_1^{\prime}(t)=-\lambda_1P_1(t)+\lambda_2P_2(t)\\ &P_2^{\prime}(t)=\lambda_1P_1(t)-\lambda_2P_2(t)\\ \end{split} \tag{23.2} \end{equation}$

Proof. We start with consider $$P(X(t+h)=\text{odd})$$, we have $\begin{equation} \begin{split} P(X(t+h)=\text{odd})&=\sum_iP(X(t+h)=\text{odd}|X(t)=i)P(X(t)=i)\\ &=P(X(t+h)=\text{odd}|X(t)=\text{even})P(X(t)=\text{even})\\ &+P(X(t+h)=\text{odd}|X(t)=\text{odd})P(X(t)=\text{odd}) \end{split} \tag{23.3} \end{equation}$ using (23.1), we have $\begin{equation} \begin{split} P(X(t+h)=\text{odd})&=(\lambda_2 h+o(h))P(X(t)=\text{even})\\ &+(1-\lambda_1 h+o(h))P(X(t)=\text{odd}) \end{split} \tag{23.4} \end{equation}$ Now denote $$P_1(t)=P(X(t)=\text{odd})$$ and $$P_2(t)=P(X(t)=\text{even})$$. By (23.4) we have $\begin{equation} \begin{split} P_1(t+h)&=(\lambda_2 h+o(h))P_2(t)+(1-\lambda_1 h+o(h))P_1(t)\\ &=\lambda_2 hP_2(t)+(1-\lambda_1 h)P_1(t)+o(h) \end{split} \tag{23.5} \end{equation}$ which implies $\begin{equation} \frac{P_1(t+h)-P_1(t)}{h}=-\lambda_1 P_1(t)+\lambda_2 P_2(t)+\frac{o(h)}{h} \tag{23.6} \end{equation}$
Take the limit as $$h\to 0$$ on both side, we get $\begin{equation} P_1^{\prime}(t)=-\lambda_1P_1(t)+\lambda_2P_2(t) \tag{23.7} \end{equation}$

Very similarly, we can get the other differential equation $\begin{equation} P_2^{\prime}(t)=\lambda_1P_1(t)-\lambda_2P_2(t) \tag{23.8} \end{equation}$ The boundary conditions are \begin{equation} \left\{\begin{aligned} & P_1(0)=0\\ &P_2(0)=1 \end{aligned}\right. \tag{23.9} \end{equation}

Equation (23.7) and (23.8) can be combined to write in matrix form as $\begin{equation} \mathbf{P}^{\prime}(x)=\begin{pmatrix} P^{\prime}_1(x)\\P^{\prime}_2(x)\end{pmatrix}= \begin{pmatrix} -\lambda_1 & \lambda_2\\ \lambda_1 & -\lambda_2 \end{pmatrix} \begin{pmatrix} P_1(x)\\P_2(x)\end{pmatrix}=\boldsymbol{\Lambda}\mathbf{P}(x) \tag{23.10} \end{equation}$
Suppose $$\mathbf{P}(x)=\boldsymbol{\eta}e^{rt}$$, then $$\mathbf{P}^{\prime}(x)=r\boldsymbol{\eta}e^{rt}$$, substitute into (23.10), we have $\begin{equation} (\boldsymbol{\Lambda}-r \mathbf{I})\boldsymbol{\eta}e^{rt}=\mathbf{0} \tag{23.11} \end{equation}$ since $$e^{rt}$$ are not zero, we can drop it and finally get
$\begin{equation} (\boldsymbol{\Lambda}-r \mathbf{I})\boldsymbol{\eta}=\mathbf{0} \tag{23.12} \end{equation}$
The matrix $$\boldsymbol{\Lambda}$$ has two distinct eigenvalues $$r_1=0$$ and $$r_2=-\lambda_1-\lambda_2$$, with corresponding eigenvector $$\begin{pmatrix} \frac{\lambda_2}{\lambda_1}& 1\end{pmatrix}^T$$ and $$\begin{pmatrix} -1& 1\end{pmatrix}^T$$, therefore, the solution to (23.10) is $\begin{equation} \mathbf{P}(x)=c_1\begin{pmatrix} \frac{\lambda_2}{\lambda_1}\\ 1\end{pmatrix}+c_2e^{-(\lambda_1+\lambda_2)t}\begin{pmatrix} -1\\ 1\end{pmatrix}^T \tag{23.13} \end{equation}$
Since the boundary condition is $$\mathbf{P}(0)=\begin{pmatrix} 0& 1\end{pmatrix}^T$$, we can find $$c_1=\frac{\lambda_1}{\lambda_1+\lambda_2}$$ and $$c_2=\frac{\lambda_2}{\lambda_1+\lambda_2}$$. Thus, we finally get $\begin{equation} \begin{pmatrix} P_1(x)\\P_2(x)\end{pmatrix}=\begin{pmatrix} \frac{\lambda_2}{\lambda_1+\lambda_2}(1-e^{-(\lambda_1+\lambda_2)t})\\ \frac{\lambda_2}{\lambda_1+\lambda_2}(\frac{\lambda_1}{\lambda_2}+e^{-(\lambda_1+\lambda_2)t})\end{pmatrix} \tag{23.14} \end{equation}$
Exercise 23.2 (Conditional distribution for Poisson process) If $$\{X(t):t\geq 0\}$$ is a Poisson process with rate $$\lambda$$, prove that $$X(u)|X(t)=n\sim Bin(n,\frac{u}{t})$$ for any $$u<t$$.
Proof. From Definition 12.1 and Theorem 12.1, we have that $\begin{equation} X(u)\sim Pois(\lambda u),\quad X(t)\sim Pois(\lambda t),\quad X(u)\perp \!\!\! \perp X(t)-X(u) \tag{23.15} \end{equation}$ Thus, $$X(t)-X(u)\sim Pois(\lambda (t-u))$$. Therefore, we have $\begin{equation} \begin{split} P(X(u)=j|X(t)=n)&=\frac{P(X(u)=j,X(t)=n)}{P(X(t)=n)}\\ &=\frac{P(X(u)=j)P(X(t)-X(u)=n-j)}{P(X(t)=n)}\\ &=\frac{\frac{(\lambda u)^j}{j!}e^{-\lambda u}\times \frac{(\lambda (t-u))^{n-j}}{(n-j)!}e^{-\lambda (t-u)}}{\frac{(\lambda t)^n}{n!}e^{-\lambda t}}\\ &=\frac{n!}{j!(n-j)!}(\frac{u}{t})^j(1-\frac{u}{t})^{n-j} \end{split} \tag{23.16} \end{equation}$ Thus, $$X(u)|X(t)=n\sim Bin(n,\frac{u}{t})$$ as we desired.
Exercise 23.3 (Distribution of arrival times for Poisson process) Let $$\{X(t):t\geq 0\}$$ be a Poisson process with rate $$\lambda$$. If $$T_1,\cdots,T_n$$ are arrival times for the $$n$$ events, show that $$P(T_1\leq t_1,\cdots,T_n\leq t_n|X(t)=n)$$ is free of $$\lambda$$. In fact, given $$X(t)=n$$, $$T_1,\cdots,T_n$$ are jointly distributed as the distribution of the order statistics from a sample of $$n$$ observations taken from the uniform distribution on $$[0,t]$$. You do not need to show the second part.
Proof. We only need to consider the case when $$0=t_0<t_1\leq t_2\leq t_3\cdots\leq t_n\leq t_{n+1}=t$$. In that case, $\begin{equation} \begin{split} &P(T_1\leq t_1,\cdots,T_n\leq t_n|X(t)=n)=\frac{P(T_1\leq t_1,\cdots,T_n\leq t_n,X(t)=n)}{P(X(t)=n)}\\ &=\frac{\sum_{x_1+\cdots+x_{n+1}=n}P(X(t_1)=x_1,X(t_2)-X(t_1)=x_2,\cdots,X(t)-X(t_n)=x_{n+1})}{P(X(t)=n)}\\ &=\frac{\sum_{x_1+\cdots+x_{n+1}=n}P(X(t_1)=x_1)P(X(t_2)-X(t_1)=x_2)P(X(t)-X(t_n)=x_{n+1})}{P(X(t)=n)}\\ &=\sum_{x_1+\cdots+x_{n+1}=n}\frac{\prod_{i=1}^{n+1}\frac{(\lambda (t_i-t_{i-1}))^{x_i}}{x_i!}e^{-\lambda(t_i-t_{i-1})}}{\frac{(\lambda t)^n}{n!}e^{-\lambda t}}\\ &=\sum_{x_1+\cdots+x_{n+1}=n}\frac{\lambda^{\sum_{i=1}^{n+1}x_i}e^{-\lambda\sum_{i=1}^{n+1}(t_i-t_{i-t})}}{\lambda^n e^{-\lambda t}}\frac{{n \choose {x_1\cdots x_{n+1}}}\prod_{i=1}^{n+1}(t-t_{i-1})^{x_i}}{t^n}\\ &=\sum_{x_1+\cdots+x_{n+1}=n}\frac{{n \choose {x_1\cdots x_{n+1}}}\prod_{i=1}^{n+1}(t-t_{i-1})^{x_i}}{t^n} \end{split} \end{equation}$
which is free of $$\lambda$$ as we desired.
Exercise 23.4 (Relationship of two independent Poisson processes) Consider two independent Poisson processes $$X(t)$$ and $$Y(t)$$ such that $$E(X(t))=\lambda t$$ and $$E(Y(t))=\mu t$$. Let two successive events of $$X(t)$$ process occur at times $$T$$ and $$T^{\prime}>T$$, so that $$X(t)=X(T)$$ for $$T\leq t<T^{\prime}$$ and $$X(T^{\prime})=X(T)+1$$. Define $$N=Y(T^{\prime})-Y(T)$$ be the random variable that denotes the number of events of the $$Y(t)$$ process between $$T$$ and $$T^{\prime}$$. Show that $\begin{equation} P(N(t)=m)=\frac{\lambda}{\lambda+\mu}(\frac{\mu}{\lambda+\mu})^m,\quad m=0,1,2,\cdots \tag{23.17} \end{equation}$
Proof. Consider the Poisson process with rate $$\lambda+\mu$$, then independently decide for each event whether it belongs to the first process, with probability $$\frac{\lambda}{\lambda+\mu}$$, or the second process, with probability $$\frac{\mu}{\lambda+\mu}$$. Then the result two processes are just $$X(t)$$ and $$Y(t)$$ described in the problem. The probability we are interested in is the probability that before 1 event happens in the process $$X(t)$$, $$m$$ events happen in the process $$Y(t)$$. This is therefore a geometric random variable with probability of success parameter $$\frac{\mu}{\lambda+\mu}$$. Thus, we have (23.17) as desired.

Exercise 23.5 (Linear birth and death process, expected number of individuals) Consider a birth and death process $$\{X(t):t\geq 0\}$$ with $$\lambda_n=n\lambda+a$$ and $$\mu_n=n\mu$$, with $$\lambda,\mu,a>0$$. If the population starts with $$i$$ individuals, prove that \begin{equation} M(t)=E[X(t)]=\left\{\begin{aligned} &at+i & \lambda=\mu\\ & \frac{a}{\lambda-\mu}\{e^{(\lambda-\mu)t}-1\}+ie^{(\lambda-\mu)t} & \lambda\neq \mu\end{aligned}\right. \tag{23.18} \end{equation}

Proof. If we define $$p_n(t)=P(X(t)=n)$$, then we have showed in class that $\begin{equation} p_n^{\prime}(t)=-(\lambda_n+\mu_n)p_n(t)+\lambda_{n-1}p_{n-1}(t)+\mu_{n+1}p_{n+1}(t) \tag{23.19} \end{equation}$

Substitute in $$\lambda_n=n\lambda+a$$ and $$\mu_n=n\mu$$, we have $\begin{equation} p_n^{\prime}(t)=-(n\lambda+a+n\mu)p_n(t)+((n-1)\lambda+a)p_{n-1}(t)+(n+1)\mu p_{n+1}(t) \tag{23.20} \end{equation}$

Then since $\begin{equation} M(t)=E(X(t))=\sum_{n=1}^{\infty}np_n(t) \tag{23.21} \end{equation}$ taking derivatives with respect to $$t$$ and substitute in (23.20) we can get $\begin{equation} \begin{split} M^{\prime}(t)&=\sum_{n=1}^{\infty}np_n^{\prime}(t)\\ &=\sum_{n=1}^{\infty}n[-n(\lambda+\mu)p_n(t)-ap_n(t)+(n-1)\lambda p_{n-1}(t)\\ &+ap_{n-1}(t)+(n+1)\mu p_{n+1}(t)]\\ &=-(\lambda+\mu)\sum_{n=1}^{\infty}n^2p_n(t)+\lambda\sum_{n=1}^{\infty}n(n-1)p_{n-1}(t)+\mu\sum_{n=1}^{\infty}n(n+1)p_{n+1}(t)\\ &-a\sum_{n=1}^{\infty}np_n(t)+a\sum_{n=1}^{\infty}np_{n-1}(t) \end{split} \tag{23.22} \end{equation}$ Using the result from the class notes (Equation (13.18)), we have $\begin{equation} \begin{split} M^{\prime}(t)&=\lambda M(t)-\mu M(t)+a\sum_{n=0}^{\infty}p_n(t)\\ &=\lambda M(t)-\mu M(t)+a \end{split} \tag{23.23} \end{equation}$

Firstly, consider the special case, if $$\lambda=\mu$$, then the differential equation reduced to $\begin{equation} M^{\prime}(t)=a \tag{23.24} \end{equation}$ which has the solution $\begin{equation} M(t)=M(0)+at \tag{23.25} \end{equation}$ Note that $$M(0)=E(N(0))=i$$ for a this linear birth and death process. Thus, $\begin{equation} M(t)=at+i \tag{23.26} \end{equation}$

In addition, if $$\lambda\neq \mu$$, the differential equation is $\begin{equation} M^{\prime}(t)-(\lambda-\mu)M(t)=a \tag{23.27} \end{equation}$ From ODE class, for a differential equation of the form $\begin{equation} \frac{dy}{dx}+P(x)y=Q(x),\quad Q(x)\not\equiv 0 \tag{23.28} \end{equation}$ Its solution is $\begin{equation} y=Ce^{-\int P(x)dx}+e^{-\int P(x)dx}\int Q(x)e^{\int P(x)dx}dx \tag{23.29} \end{equation}$

For our specific problem, we have $\begin{equation} \begin{split} M(t)&=Ce^{\int_0^t(\lambda-\mu)dt}+e^{\int_0^t(\lambda-\mu)dt}\int_0^tae^{-\int_0^t(\lambda-\mu)dt}dt\\ &=Ce^{(\lambda-\mu)t}+e^{(\lambda-\mu)t}a\int_0^te^{-(\lambda-\mu)t}dt\\ &=Ce^{(\lambda-\mu)t}+e^{(\lambda-\mu)t}a[\frac{1}{\lambda-\mu}-\frac{1}{\lambda-\mu}e^{-(\lambda-\mu)t}]\\ &=Ce^{(\lambda-\mu)t}+\frac{a}{\lambda-\mu}\{e^{(\lambda-\mu)t}-1\} \end{split} \tag{23.30} \end{equation}$

The constant $$C$$ need to be solved from the boundary condition $$M(0)=i$$, substitute $$t=0$$ in (23.30), we have $$C=i$$. Thus, we finally get $\begin{equation} M(t)=ie^{(\lambda-\mu)t}+\frac{a}{\lambda-\mu}\{e^{(\lambda-\mu)t}-1\} \tag{23.31} \end{equation}$ as we desired.

Exercise 23.6 (Poisson process, arrival time) A cable car starts off with $$n$$ riders. The times between successive stops of the car are independent exponential random variables with rate $$\lambda$$. At each stop one rider gets off. This takes no time and no additional riders get on. After a rider gets off the car, he or she walks home. Independently of all else, the walk takes an exponential time with rate $$\lambda$$.

1. What is the distribution of time at which the last rider departs the car?

2. Suppose the last rider departs the car at time $$t$$. What is the probability that the $$i$$th rider is in home by that time, $$i=1,\cdots,n$$?

Proof. For part (a), let $$T$$ be the random variable we care about. Then $$T$$ is a sum of $$n$$ independent exponential random variables with rate $$\lambda$$. Therefore, $$T\sim Gamma(n,\lambda)$$.

For part (b), suppose a rider gets off at time $$s$$, then at time $$t$$, the probability that this rider has not arrived at home is $\begin{equation} \int_{t-s}^{\infty}\lambda e^{\lambda x}dx=e^{-\lambda(t-s)} \tag{23.32} \end{equation}$ Given that the last rider departs the car at time $$t$$, the time that the other $$n-1$$ rider gets off follows a uniform distribution on $$[0,t]$$. Hence, the $$i$$th rider is not at home by $$t$$ has the probability $\begin{equation} \int_0^{t}e^{-\lambda(t-s)}\cdot\frac{1}{t}ds=\frac{1-e^{-\lambda t}}{\lambda t} \tag{23.33} \end{equation}$ Thus, the probability that the $$i$$th rider is in home by that time, for $$i=1,\cdots,n$$, is \begin{equation} P=\left\{\begin{aligned} & 1-\frac{1-e^{-\lambda t}}{\lambda t} & i=1,\cdots,n-1\\ & 0 & i=n\end{aligned}\right. \tag{23.34} \end{equation}

Exercise 23.7 (Compound Poisson process and its application) Let $$\{N(t):t\geq 0\}$$ be a Poisson process with rate $$\lambda$$. Define a sequence of nonnegative, independent and identically distributed random variables $$\{D_i:i\geq 1\}$$ independent from $$N(t)$$. A stochastic process $$\{Y(t):t\geq 0\}$$ is a compound Poisson process if $$Y(t)=\sum_{i=1}^{N(t)}D_i$$.

1. Find $$E[Y(t)]$$ and $$Cov(Y(t),Y(s))$$.

2. Customers arrive at an automatic teller machine (ATM) in accordance with a Poisson process with rate 12 per hour. The amount of money withdrawn on each transaction is a random variable with mean $30 and standard deviation$50. (A negative withdrawal means that money was deposited.) Suppose that the machine is in use 15 hours per day. Formulate this scenario as a compound Poisson process to find the expected amount of money withdrawn per day. Can you provide an approximate probability that the total daily withdraw is greater than $5000? Proof. For part (a), by Wald identity, we have $\begin{equation} E(Y(t))=E(D_1+\cdots+D_{N(t)})=E(N(t))E(D_1)=\lambda tE(D_1) \tag{23.35} \end{equation}$ As for the covariance, firstly notice that $\begin{equation} \begin{split} Var(Y(t))&=E(Var(Y(t)|N(t)))+Var(E(Y(t)|N(t)))\\ &=E(N(t)Var(D))+Var(N(t)E(D))\\ &=Var(D)E(N(t))+E(D)^2Var(N(t))\\ &=Var(D)\lambda t+E(D)^2\lambda t\\ &=\lambda tE(D^2) \end{split} \tag{23.36} \end{equation}$ Assume w.l.o.g. that $$t<s$$, then we have $\begin{equation} \begin{split} Cov(Y(t),Y(s))&=Cov(Y(t),Y(s)-Y(t)+Y(t))\\ &=Cov(Y(t),Y(t-s))+Var(Y(t))=Var(Y(t))=\lambda tE(D^2) \end{split} \tag{23.37} \end{equation}$ Therefore, in general we have $\begin{equation} Cov(Y(t),Y(s))=\lambda \min\{s,t\}E(D^2) \tag{23.38} \end{equation}$ For part (b), let $$Y(t)$$ be the total amount of money withdrawn in the interval $$[0,t]$$, where the time $$t$$ is measured in hours. Assuming that the successive amounts withdrawn are independent and identically distributed random variables, the stochastic process $$\{Y(t):t\geq 0\}$$ is then a compound Poisson process, and $$Y(15)$$ denotes the daily withdraw. Its mean and variance can be compute using (23.35) and (23.36), that is $\begin{equation} \begin{split} &E(Y(15))=12\times 15\times30=5400\\ &Var(Y(15))=12\times 15\times(30^2+50^2)=612000 \end{split} \tag{23.39} \end{equation}$ Therefore, by CLT we have $\begin{equation} P(Y(t)\geq 5000)=P(Z\geq \frac{5000-5400}{\sqrt{612000}})\approx 0.6954 \tag{23.39} \end{equation}$ Thus, the approximate probability that the total daily withdraw is greater than$5000 is 0.6954.

Exercise 23.8 (Process that descirbe the decay of particles) At each (discrete) time point $$n=0,1,2,\cdots$$, a number $$Y_n$$ of particles enters a chamber, where the $$Y_n$$, $$n\geq 0$$, are independent and identically Poisson distributed with parameter $$\lambda$$, that is, for all $$n\geq 0$$, $$Pr(Y_n=y)=\lambda^y\exp(-\lambda)/y!$$, for $$y\in\{0,1,2,\cdots\}$$. Each particle in the chamber may decay during two successive time points with probability $$q$$ (where $$0<q<1$$) which is constant over time and the same for all particles. Moreover, particles decay independently of each other and $$Y_n$$ is independent of the number of particles that decay between time points $$n-1$$ and $$n$$. Let $$X_n$$ be the number of particles in the chamber at time $$n$$, where $$X_n$$ includes particles present just after the entry of the $$Y_n$$ particles.

1. Show that $$X=\{X_n:n\geq 0\}$$ is a time homogeneous Markov chain, and prove that its transition probabilities are given by $\begin{equation} P(X_{n+1}=j|X_n=i)=\exp(-\lambda)\sum_{r=0}^{\min\{i,j\}}\frac{i!}{(i-r)!r!(j-r)!}(1-q)^rq^{i-r}\lambda^{j-r} \tag{23.40} \end{equation}$

2. Show that the limiting probabilities for the number of particles in the chamber are given by $\begin{equation} \lim_{n\to\infty}P(X_n=j)=\exp(-\lambda q^{-1})\frac{(\lambda q^{-1})^j}{j!},\quad j\in\{0,1,2,\cdots\} \tag{23.41} \end{equation}$

Proof. For part (a), let $$Z_n$$ denote the number of particles remained in the chamber at time $$t=n$$, then we have $\begin{equation} \begin{split} P(X_{n+1}=j|X_n=i)&=\sum_{r=0}^{\min\{i,j\}}P(X_{n+1}=j|Z_n=r,X_n=i)P(Z_n=r|X_n=i)\\ &=\sum_{r=0}^{\min\{i,j\}}P(Y_{n+1}=j-r)P(Z_n=r)\\ &=\sum_{r=0}^{\min\{i,j\}}\lambda^{j-r}\exp(-\lambda)\frac{i!}{(j-r)!r!(i-r)!}(1-q)^rq^{i-r}\\ &=\exp(-\lambda)\sum_{r=0}^{\min\{i,j\}}\frac{i!}{(i-r)!r!(j-r)!}(1-q)^rq^{i-r}\lambda^{j-r} \end{split} \tag{23.42} \end{equation}$ as we desried. Since $$P(X_{n+1}=j|X_n=i)$$ is a constant as a function of time $$t$$, the Markov chain is time homogeneous.

For part (b), since $$X$$ is a irreducible Markov chain, we only need to check (23.40) and (23.41) satisfies the detailed balance condition (Proposition 10.2). In fact, for any $$i,j$$ $\begin{equation} \begin{split} \pi_ip_{ij}&=\exp(-\lambda q^{-1})\frac{(\lambda q^{-1})^i}{i!}\exp(-\lambda)\sum_{r=0}^{\min\{i,j\}}\frac{i!}{(i-r)!r!(j-r)!}(1-q)^rq^{i-r}\lambda^{j-r}\\ &=\exp(-\lambda (q^{-1}+1))\sum_{r=0}^{\min\{i,j\}}\frac{(1-q)^rq^{-r}\lambda^{i+j-r}}{(i-r)!r!(j-r)!} \end{split} \tag{23.43} \end{equation}$
and similarly, $\begin{equation} \begin{split} \pi_jp_{ji}&=\exp(-\lambda q^{-1})\frac{(\lambda q^{-1})^j}{j!}\exp(-\lambda)\sum_{r=0}^{\min\{i,j\}}\frac{j!}{(i-r)!r!(j-r)!}(1-q)^rq^{j-r}\lambda^{i-r}\\ &=\exp(-\lambda (q^{-1}+1))\sum_{r=0}^{\min\{i,j\}}\frac{(1-q)^rq^{-r}\lambda^{i+j-r}}{(i-r)!r!(j-r)!} \end{split} \tag{23.44} \end{equation}$ Thus, we have $$\pi_ip_{ij}=\pi_jp_{ji}$$, (23.41) gives the stationary distribution. Since any state of $$X$$ is non-null persistent, the stationary distribution is actually the limiting distribution.